Hematological profile of the domestic pigeon (Columba livia) from the north coast of Peru - Vásquez Sánchez, Gloria (2021)
The aim if this study was to determine the haematological profile of the pigeon (Columba livia) raised on the north coast of Peru. In total, 96 blood samples from juvenile and adult pigeons (51 females and 45 males) were used. Samples were collected in tubes with anticoagulant between April and December 2019. Natt and Herrick haematological techniques (red and white blood cell count), microhematocrit method (hematocrit), cyanmethemoglobin method (haemoglobin) and stained blood smears with Wright staining (differential leukocyte count and platelet count) were used. The values for juvenile and adult females and juvenile and adult males were 262.4±48.5, 308.8±38.0, 258.2±56.1 and 303.8±42.9 g, haematocrit of 40.8±4.9, 45.8±3.9, 40.9±3.4 and 43.6±5.2% , haemoglobin of 14.1±1.9, 15.4±1.8, 13.9±1.9 and 14.8±2.6 g/dl, red blood cell count of 3.09±1.0, 3.1±0.6, 3.0±0.8 and 3.3±0.7x106/µl, platelets of 32.4±12.9, 35.9±8.8, 33.6±12.5 and 34.0±10.7x103/µl, white blood cells of 19.8±1.4, 17.6±0.9, 18.2±1.0 and 17.0±1.0x103/µl, and heterophile/lymphocyte ratio of 1.8, 1.5, 1.7 and 1.4, respectively. The average values found were within those reported for the Columbiform order.